2012
DOI: 10.5539/ijbm.v7n20p71
|View full text |Cite
|
Sign up to set email alerts
|

The Levels of Using Strategic Management Tools and Satisfaction with Them: A Case of Five-Star Hotels in Turkey

Abstract: The main purpose of this research is to determine the levels of using strategic management tools (SMT) and satisfaction with them in five star hotels in Turkey. In addition, the relationships between the characteristics of managers and organizations in terms of using the SMT and satisfaction with term are investigated. The sample includes 53 five-star hotels in Turkey. Results show that the levels of using SMT are high, but satisfactions with them are low. While the tool with the highest usage is customer rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Tools involving a high usage level and providing a high satisfaction level are known as power tools while those involving a low usage level and providing a low satisfaction level are called rudimentary tools (Rigby & Bilodeau, 2007). In another study on this subject but which focused on hotel management in Turkey (Erbası & Unuvar, 2012), customer relationship management, total quality management, SWOT analysis and mission and vision statements were determined to be power tools. In the same study, business process reengineering and downsizing were found to be rudimentary tools.…”
Section: Discussionmentioning
confidence: 99%
“…Tools involving a high usage level and providing a high satisfaction level are known as power tools while those involving a low usage level and providing a low satisfaction level are called rudimentary tools (Rigby & Bilodeau, 2007). In another study on this subject but which focused on hotel management in Turkey (Erbası & Unuvar, 2012), customer relationship management, total quality management, SWOT analysis and mission and vision statements were determined to be power tools. In the same study, business process reengineering and downsizing were found to be rudimentary tools.…”
Section: Discussionmentioning
confidence: 99%
“…The selected firm capabilities that are thought to influence firm performance includes product research, knowledge management and technology. Ali and Şafak (2012) found out that there exist a relationship between firm capabilities and firm performance even though performance is interpreted from different perspectives from one organization to another. Yusufu (2013) observed that organizations that embraced technology in service delivery associated with customer satisfaction.…”
Section: Firm Capabilities and Firm Performancementioning
confidence: 99%
“…Firms dedicated to develop knowledge and skills of workers not only promote creativity but also innovation of products and services (Gilley & Rasheed, 2013). Technology integration in the systems not only enhances efficiency and effectiveness of the system but promotes enhanced service delivery and facilitates globalization (Ali & Şafak, 2012). With modern technologies, firms are able to market their products though alternative channels which may include direct or indirect channels (Yusufu, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation